Analisis Disparitas Distribusi Pendapatan Petani Kelapa Sawit di Kabupaten Rokan Hulu - Rahayu, Heffi Christya; Suhartono, Suhartono; Ratlalan, Justinus Edi; Fathoni, Ahmad; Gitya, Febiana (Fakultas Ekonomi Universitas Samudra, 2024)
The analysis aims to examine disparities in income distribution among oil palm farmers in Rokan Hulu Regency. Primary data consists of the results of distributing questionnaires to 100 oil palm farmers in the research location, then analyzed using the Gini coefficient and Lorenz curve methods. Research findings indicate that the income distribution gap for oil palm farmers in Rokan Hulu Regency tends to be low, meaning that the average income is almost evenly distributed. However, integration or comparison with other research locations is needed to obtain more comprehensive results.